Implementation of E-Government through the Samsat Mobile Jawa Barat at the Regional Revenue Agency of West Java Province - Rohman Hakim; Khaerul Umam; Husen Saeful Anwar (Publica: Jurnal Pemikiran Administrasi Negara, 2021)
The purpose of this study was to analyze the application of e-government through Samsat Mobile Jawa Barat at the Regional Revenue Agency of West Java Province. The theory used in this study uses e-government theory which includes (1) content development, (2) competency building, (3) connectivity, (4) cyber law, (5) citizen interface, and (6) capital. The research approach used is a qualitative approach. Data collection techniques by interview, observation and documentation. The data analysis technique is based on Creswell's thinking with a bottom-up hierarchical approach model. The results of this study indicate that the implementation of e-government through Samsat Mobile Jawa Barat in the Regional Revenue Agency of West Java Province has been running quite well. Although based on Idrajati's e-government theory, there are several criteria that need to be improved. Such as content development criteria that still do not provide an iOS-based Samsat Mobile Jawa Barat application, competency building criteria have not yet produced employees who are experts in managing the appearance of the Bapenda West Java website design and content. The connectivity criteria are good because they are in the West Java region. Cyber law criteria must be added specifically, because it only follows the rules of the central government, the citizen interface criteria still need to be developed because it only has two channels, namely the website and the android application. While the criteria for capital is sufficient, it only needs additional sources of capital apart from the APBD.